Fracture properties of concrete under cyclic loading. (26th April 2021) - Zhang, Jun; Yu, Zihao; Tang, Yuxiang; Shen, Jie; Chen, Hongniao
Highlights: Full-displacement fields of concrete beams under monotonic and cyclic loading were measured by ESPI technique. Fracture stages of concrete in an entire loading and unloading cycle were evaluated. Influences of cyclic number on crack opening and hysteretic dissipated energy were analyzed.. Abstract: Three-point bending tests were performed on pre-notched beams to investigate the fracture properties of concrete under cycling loading. Electronic speckle pattern Interferometry (ESPI) technique was used to measure the full-field displacement of the beams. The influence of loading history on the fracture properties of concrete were analyzed. Results measured by ESPI were compared with that measured by a clip gauge and good agreement was observed, which validates the reliability of using ESPI to measure the deformation of fracture process zone during crack extension. The experimental results indicate that load–displacement curves under monotonic loading are an envelope line for that under cyclic loading. The load–displacement curves of each loading cycle can be divided into five stages and in both loading and unloading process, elastic deformation responses earlier than inelastic deformation. The critical crack mouth opening displacement (CMODc) increases with the loading cycles and reaches about 0.090 mm while the critical crack tip opening displacement (CTODc) is almost constant about 0.034 mm which can be used as a fracture characteristic of the material. The cumulative dissipative energy tends to reach about 21 N/m as the loading cycles increase and can be used as a fracture parameter under cyclic loading.